Association of the interaction between occupational hazard factors and IL-1β gene polymorphism with cognitive function in electrolytic aluminum workers - Li, Youxing; Pang, Yaqin; Chen, Dongshun; Lu, Feiyu; Tian, Hongyan; Qin, Fengni; Wei, Kuntao; Ishak, Ahmad Razali Bin; Mohd Aris, Mohd Shukri Bin; Qi, Guangzi (Frontiers in Genetics, 2025)
BackgroundVarious occupational hazards in the electrolytic aluminum environment have been linked to cognitive decline. However, the interactive effects of these hazards and genetic factors on cognitive function remain unclear.ObjectiveThis study aimed to identify the primary occupational hazards, examine their interaction with IL-1β gene polymorphisms in relation to cognitive function.MethodsA cross-sectional study was conducted in June 2024 at an electrolytic aluminum company in China, involving 478 male workers. Cognitive function was assessed using the Montreal Cognitive Assessment. Calculate the cumulative exposure dose of harmful factors such as aluminum dust. Additionally, IL-1β gene polymorphisms (rs1143627, rs1143643, rs16944, rs3917356) and serum protein levels were analyzed. The associations between environmental exposure, genetic factors, and cognitive function were examined using multivariate stepwise linear regression, restricted cubic splines, generalized linear models, and hierarchical analysis. Covariance analysis and independent sample t-tests were employed to assess the potential mediating effect of peripheral blood IL-1β levels.ResultsCumulative exposure to aluminum dust was significantly associated with cognitive decline (β = −0.18, 95% CI: 0.27, −0.10), and the relationship was linear. Compared to the wild genotype, individuals carrying rs1143627 G/G, rs1143643 C/C, and rs16944 A/A exhibited significantly lower cognitive scores (P < 0.01), whereas rs3917356 C/T and T/T conferred a protective effect (P < 0.01). The model was adjusted for age, body mass index, and cumulative aluminum dust exposure. The genetic effect associated with IL-1β was more pronounced in individuals with high aluminum exposure (>2.37 mg/m3 × year). IL-1β serum protein levels showed no significant association with cognitive function (P > 0.05).ConclusionCumulative exposure to aluminum dust is a key risk factor for cognitive decline. IL-1β polymorphisms influence susceptibility, with the effect becoming more pronounced under high aluminum exposure. However, peripheral blood IL-1β levels do not mediate this association with cognitive decline.